The Aarhus Convention and the experience of public participation in environmental impact assessments - Devane, Denis John (2016)
Public participation in the environmental impact assessment (EIA) process is essential to expediting societies’ shift from fossil fuels to renewable energies such as wind power. The current state of public participation in EIAs is highly contested as the debate on what can be done to improve it continues. The primary focus of the thesis is to study public participation and its use in an Irish EIA. It aims to explore exactly how stakeholders of the Lisheen Wind Farm case experienced the public participation offered to them and to what extent did it abide by the main three principal pillars of the Aarhus Convention. The research approach adopted in this thesis utilises an explorative case study approach. By choosing a single representative case study the thesis can concentrate on assessing how the public participation was conducted as well as exploring the experiences of the participants. Qualitative methods were predominately used as the thesis adopted a dual analysis approach utilising practice evaluation criteria and phenomenological methods. The case study findings showed that all of the practice evaluation criteria were fulfilled. However; the results also displayed the weaknesses that are still present in public participation today, such as poor information provision, poor facilitation and the existence of monetary barriers. The phenomenological analysis, with its focus on more subjective elements, found that social factors such as civic duty and self-perception can affect how much participants engage in the participation process. The conclusions drawn from the case study findings are, firstly, that the public participation in the case adhered to the primary principals of the Aarhus Convention. Secondly that deeper insights gathered from the experiences of participants are an underutilised and could be valuable asset in the goal of improving public participation in EIAs.